Properties of an Antigenic Glycoprotein Isolated from Influenza Virus Hemagglutinin - Eckert, Edward A. (1973)
A purified antigen, HABA protein, has been derived from influenza virus concentrates by extraction with denaturing solvents. The protein lacks hemagglutinating activity but binds completely strain-specific, hemagglutination-inhibiting antibodies and induces neutralizing antibodies in experimental animals. Physicochemical characterization of HABA protein identifies it as a single homogeneous glycoprotein with a molecular weight of 78,000. On dissociation with guanidine or sodium dodecyl sulfate, in the presence of reducing agents, only one size of polypeptide with a molecular weight of the order of 40,000 is characteristic of the preparations. The data indicate that HABA protein is a dimer of HA(1) polypeptide of the influenza virus hemagglutinin substructure, and that only trace amounts of other polypeptides are present.